The role of nanocomposites against biofilm infections in humans - Varma, Anand; Warghane, Ashish; Dhiman, Neena K.; Paserkar, Neha; Upadhye, Vijay; Modi, Anupama; Saini, Rashmi (Frontiers in Cellular and Infection Microbiology, 2023)
The use of nanomaterials in several fields of science has undergone a revolution in the last few decades. It has been reported by the National Institutes of Health (NIH) that 65% and 80% of infections are accountable for at least 65% of human bacterial infections. One of their important applications in healthcare is the use of nanoparticles (NPs) to eradicate free-floating bacteria and those that form biofilms. A nanocomposite (NC) is a multiphase stable fabric with one or three dimensions that are much smaller than 100 nm, or systems with nanoscale repeat distances between the unique phases that make up the material. Using NC materials to get rid of germs is a more sophisticated and effective technique to destroy bacterial biofilms. These biofilms are refractory to standard antibiotics, mainly to chronic infections and non-healing wounds. Materials like graphene and chitosan can be utilized to make several forms of NCs, in addition to different metal oxides. The ability of NCs to address the issue of bacterial resistance is its main advantage over antibiotics. This review highlights the synthesis, characterization, and mechanism through which NCs disrupt Gram-positive and Gram-negative bacterial biofilms, and their relative benefits and drawbacks. There is an urgent need to develop materials like NCs with a larger spectrum of action due to the rising prevalence of human bacterial diseases that are multidrug-resistant and form biofilms.